Phytase and Acid Phosphatase Activity III Seeds of Arid Zone Crops - Niwas, Ram; Yadav, R S; Tparafdar, J C (Annals of Arid Zone, 2016)
The phytase and acid phosphatase activity of legumes, cereals and oilseeds were measured in seeds. The genotypic differences in pearl millet, moth bean and mustard were also determined. In general, legume seeds showed higher phytase and acid phosphatase activity followed by cereals and oilseeds. Clusterbean and chickpea seeds had highest phytase and acid phosphatase activity, respectively, while sesame showed lowest activity of both the enzymes. The phytase activity in the seeds was 21 to 59 times higher than acid phosphatase. The genotypic differences among the cultivars was up to 115% in phytase activity and 23% in acid phosphatase activity. The highest phytase activity was observed in RMM-12 (moth bean), CZP;9603 (pearl millet) and SAL-12 (mustard) cultivars. The maximum acid phosphatase activity was observed in RM0-435 (m,oth bean), CZP-9701 (pearl millet) and CSTR-338-l (mustard) genotypes. The results suggested that seed stored a large amount of phytase along with acid phosphatase and it varied among the genotypes. The higher activity of these enzymes in seeds may have high ability to exploit organic P and sustain in P deficient condition.